Evaluasi Penggunaan Modul Ajar Bahasa Indonesia Siswa di SD Negeri 29 Ampenan dengan Metode Didactical Suitability - Muhammad Hafsil; Asrin; Mohammad Archi Maulyda (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
This study aims to evaluate the feasibility of an Indonesian language teaching module based on six didactic components: epistemic, cognitive, interactional, mediational, affective, and ecological at State Elementary School 29 Ampenan. This study is an evaluative study with a qualitative approach using the Didactical Suitability model . Most previous studies have focused on the effectiveness of teaching modules in improving learning outcomes, whereas studies evaluating the quality of teaching modules using the Didactical Suitability framework remain very limited. Data were collected through structured observations, in-depth interviews, and module documentation, then analyzed descriptively qualitatively using the Miles and Huberman method. The results show that the teaching module generally fully meets the epistemic and interactional components, but there are still shortcomings in several cognitive, mediational, affective, and ecological indicators. For example, some students are less active in reading the module, and in one class the learning atmosphere is not fully conducive. Interviews with teachers indicate that the module is easy to use and relevant to students' needs, but module evaluation has not been carried out optimally. This study contributes to the development of Didactical Suitability-based evaluation of teaching materials in Indonesian language learning in elementary schools and serves as a basis for teachers and schools to improve the quality of teaching modules to better suit the needs and characteristics of students.